Visuospatial asymmetries do not modulate the cheerleader effect - Carragher, Daniel J. (Sci Rep, 2018)
The cheerleader effect occurs when the same individual appears to be more attractive when seen in a group, compared to alone. As observers over-attend to visual information presented in the left visual field, we investigated whether the spatial arrangement of the faces in a group would influence the magnitude of the cheerleader effect. In Experiment 1, target faces were presented twice in the centre of the display: once alone, and once in a group. Group images featured two distractor faces, which were presented in either the left or the right visual field, or on either side of the target. The location of the distractor faces did not modulate the size of the cheerleader effect, which was observed in each group configuration. In Experiment 2, we manipulated the location of the target faces, which were presented at the far left, far right, or centre of the group. Faces were again significantly more attractive in each group configuration, and the spatial location of the target face did not influence the size of the cheerleader effect. Together, our results show that the cheerleader effect is a robust phenomenon, which is not influenced by the spatial arrangement of the faces in the group.